Differential Selling Strategies Between Investors and Consumers: Evidence from the Chinese Housing Market. Issue 1 (2nd January 2022) - Deng, Kuang Kuang; Chen, Jie; Lin, Zhenguo; Yang, Xianling
Abstract: We investigated how real estate selling behaviors and transaction outcomes vary with sellers' motivations. By exploring a unique dataset of residential sales in Beijing, China, we were able to distinguish between consumer sellers and investor sellers. Consumer sellers engage in chained transactions (i.e., selling one and buying another property in parallel for upsizing their houses through moving to a better location or trading for a larger property). The consumer sellers differ from investor sellers, who sell for cashing out capital gains, in selling strategies due to their liquidity constraints and higher search costs in the chained transactions. Our empirical analyses reveal that, for successful transactions, consumer sellers list and sell their properties at higher prices than investor sellers, all else being equal; however, the price premiums are achieved without longer time on the market due to their strategy of searching more intensively. This article provides additional insights on how real estate sellers' credit constraints and opportunity costs of searching govern the selling strategies and transaction outcomes of property trading.